My answer is different when I follow the PEMDAS rule.
If you write out the steps you took maybe we can figure out where is your error
Here is my solution, let me know if i got the right solution
= 12 - 20 / 4 + 3 * (-2)²
= 12 - 20 / 4 + 3 * 4
= 12 - 20 / 4 + 12
= 12 - 5 + 12
Your answer is right!
Can you please explain the step
yes of course
12-5+12 = 24-5 = 19
But why we didn’t solve -5+12, first?
You should have solved in that order first to respect the parenthesis, but since 12+12-5 is the same as 12-5+12 i did it in a different order, i hope it won’t confuse you.
Yes I understand because according to PEMDAS rule we have to add before subtracting and if we solve -5+12 it becomes subtraction instead of addition. I hope I made reasonable logic…